Pembuatan Turn Based Strategy Role Playing Game Menggunakan Unity Game Engine - Andre Lionel Sanjaya; Gregorius Satia Budhi; Liliana Liliana (Jurnal Infra, 2015)
Strategy is one of the more popular video game genres. There are many factors that can affect whether a strategy game is good or not. Some of those are the graphics of the game, the menus and features, and also the AI inside the game. This game is made with that understanding.The game will be made with Unity Game Engine. ID3 and Backpropagation will be used as the AIs in this game. The game is divided into two parts, namely the exploration mode and the battle mode. In the exploration mode, the player can freely explore their surrounding environment, interact with NPCs, or encounter an enemy. Battle mode is a mode where the player fights the enemy they encounters. Battle mode will be played in a grid that resembles a chessboard. The game will go into this mode only if the player made contact with the enemy in exploration mode. When the battle is finished, the player will return to exploration mode.The resulting games are tested by playing the game from start to finish. From the results, it can be concluded that the game has implemented the general features of games in strategy and RPG genre.